Effects of two training phases of different intensities on the exercise-induced hormonal response and psychological parameters in endurance athletes - Urhausen, A.; Gabriel, H. H.; Brückner, F.; Kindermann, W. (International Journal of Sports Medicine, 1998)
Zielstellung: Untersuchung des Pathomechanismus und früher diagnostischer Kriterien eines Überlastungssysndroms.